Model for opportunities assessment to increase the enterprise innovation activity - Frolova, Larysa; Zhadko, Kostiantyn; Ilyash, Olha; Yermak, Svitlana; Nosova, Tetiana (Business: Theory and Practice, 2021)
This study shows that the model of assessing the opportunities for innovation activity of enterprises is multivariate and interrelated with such macroeconomic regulators of Ukraine’s development as competitive attractiveness of the country, favorable conditions for doing business in the country and innovation activity of enterprises. The use of a three-dimensional matrix of indicators to assess Ukraine’s competitive attractiveness allowed us to evaluate the significant impact of changes in Ukraine’s Global Innovation Index on the innovation activity of enterprises for the period 2014–2019. Moreover, the greater the value of the indicator of the state’s innovation potential is, the higher the level of innovation activity in the country becomes, which significantly increases the positive image of Ukrainian entrepreneurs at the global level and acts as a “green light” for foreign investors. Given the wide range of parameters that must be taken into account in an integrated assessment of innovation activity of an enterprise, we have used the method of component analysis. The uniqueness of an integrated assessment of innovation activity of an enterprise is carried out in accordance with the concept of value formation of innovations and it is tested on the example of Ferrotrading LLC. The effectiveness of the study consists in the fact that the selected sub-indicators for assessing the innovation activity of the studied enterprise (innovation resources, innovation competencies and innovation abilities) greatly complement the assessment of the opportunities for innovation activity in the proposed model. The conducted study has theoretical and practical significance. It can be used as a basis for further research in this area and can be employed by governments to make management decisions on increasing the innovation activity of business and the state as a whole.